Modern cartilage imaging of the ankle - Weber, Marc-André; Wünnemann, Felix; Rehnitz, Christoph (RöFo, 2017)
Background Talar osteochondral lesions are an important risk factor for the development of talar osteoarthritis. Furthermore, osteochondral lesions might explain persistent ankle pain. Early diagnosis of accompanying chondral defects is important to establish the optimal therapy strategy and thereby delaying or preventing the onset of osteoarthritis. The purpose of this review is to explain modern cartilage imaging with emphasis of MR imaging as well as the discussion of more sophisticated imaging studies like CT-arthrography or functional MR imaging. Methods Pubmed literature search concerning: osteochondral lesions, cartilage damage, ankle joint, talus, 2 D MR imaging, 3 D MR imaging, cartilage MR imaging, CT-arthrography, cartilage repair, microfracture, OATS, MACT. Results and Conclusion Dedicated MR imaging protocols to delineate talar cartilage and the appearance of acute and chronic osteochondral lesions were discussed. Recent developments of MR imaging, such as isotropic 3 D imaging that has a higher signal-to noise ratio when compared to 2 D imaging, and specialized imaging methods such as CT-arthrography as well as functional MR imaging were introduced. Several classifications schemes and imaging findings of osteochondral lesions that influence the conservative or surgical therapy strategy were discussed. MRI enables after surgery the non-invasive assessment of the repair tissue and the success of implantation. Key points Citation Format
Gesehen am 03.04.2019